2021
DOI: 10.3390/su132312996
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Labor Market: An Analysis of Supply and Demand in the Spanish Municipalities

Abstract: The COVID-19 pandemic represents the largest health and economic crisis in recent history. It has particularly affected the countries of the Mediterranean area, with serious repercussions in terms of not only infections and deaths, but also economic losses. In particular, social distancing measures, severe restrictions, and lockdowns imposed by governments have had serious repercussions on the labor market. The impact of the pandemic on the labor market has prompted numerous researchers to examine and quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Measures aimed at reducing labour force participation and social interaction (such as restrictions to curb the pandemic) reduce the demand for labour and indirectly contribute to higher unemployment rates. Raimo et al (2021) studied the impact of the pandemic on the labour market in individual Spanish municipalities and tried to determine the impact of restrictions on labour supply and demand, in addition to factors that affect employment levels. They found that employment during the first months of the pandemic was influenced by the characteristics of the business structure and showed the relationship between the economic activity of the municipality and the demographic characteristics of its population, which shape the regional labour market (Raimo et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Measures aimed at reducing labour force participation and social interaction (such as restrictions to curb the pandemic) reduce the demand for labour and indirectly contribute to higher unemployment rates. Raimo et al (2021) studied the impact of the pandemic on the labour market in individual Spanish municipalities and tried to determine the impact of restrictions on labour supply and demand, in addition to factors that affect employment levels. They found that employment during the first months of the pandemic was influenced by the characteristics of the business structure and showed the relationship between the economic activity of the municipality and the demographic characteristics of its population, which shape the regional labour market (Raimo et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Raimo et al (2021) studied the impact of the pandemic on the labour market in individual Spanish municipalities and tried to determine the impact of restrictions on labour supply and demand, in addition to factors that affect employment levels. They found that employment during the first months of the pandemic was influenced by the characteristics of the business structure and showed the relationship between the economic activity of the municipality and the demographic characteristics of its population, which shape the regional labour market (Raimo et al, 2021). Svabova et al (2020) describe the evolution of the unemployment rate and the number of newly registered unemployed in Slovakia from November 2019 to October 2020, i.e., during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A nemzetközi szakirodalomban leírtak szerint a koronavírus válság azon kívül, hogy kihatott a vállalkozások pénzügyi helyzetére és piaci viszonyaira, a napi működésre is jelentős hatással volt (Arshed et al, 2021, Shinozaki és Rao, 2021. A napi működési rend változása elsősorban a szervezetek foglalkoztatási jellemzőit érintette (Raimo et al, 2021). Reagálva a koronavírus okozta helyzetre sok kis-és középvállalkozás esetében megváltoztak munkamódszerek, álltalánossá és elterjedtté vált a távmunka (Pulido-Martos et al, 2021).…”
Section: áBra: Milyen Hatással Volt a Koronavírus Válság Az öN Vállal...unclassified
“…The structural transformation of the employment market is characterized by a high degree of dynamism and contradiction, which, in the realities of the pandemic caused by SARS-CoV-2, is manifested in trends of uncertainty, unpredictability and crisis of its development (Raimo et al, 2021). Total restrictive measures imposed in recent months by most countries have had a very negative impact on the operation of all labor market subjects, sometimes causing a crisis of a more global, psychological nature -the loss of a sense of certainty and transparency about their own future, deprivation of basic needs, professional and social marginalization, and loss of the meaning in life (Trógolo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%